2010
DOI: 10.1111/j.1399-5618.2010.00861.x
|View full text |Cite
|
Sign up to set email alerts
|

From BALANCE to DSM‐5: taking lithium seriously

Abstract: Ghaemi SN. From BALANCE to DSM‐5: taking lithium seriously.
Bipolar Disord 2010: 12: 673–677. © 2010 The Author.
Journal compilation © 2010 John Wiley & Sons A/S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Comparing VPA with Li, Geddes et al (2010) found that VPA monotherapy was less effective than Li monotherapy at preventing relapse episodes (hazard ratio, 0.71; confidence interval:0.051-1.00, P = 0.0472). The BALANCE study also questioned the use of VPA over Li as a first-line and prophylactic antimanic agent (Ghaemi, 2010;Nivoli et al, 2012). Similar to our study, Davis et al (1999) carried out a meta-analysis of 10 double-blind randomized studies comparing relapse rates and found that the difference between the effectiveness of Li and CBZ was nonsignificant: 60% for Li patients and 55% for CBZ.…”
Section: Discussionsupporting
confidence: 58%
“…Comparing VPA with Li, Geddes et al (2010) found that VPA monotherapy was less effective than Li monotherapy at preventing relapse episodes (hazard ratio, 0.71; confidence interval:0.051-1.00, P = 0.0472). The BALANCE study also questioned the use of VPA over Li as a first-line and prophylactic antimanic agent (Ghaemi, 2010;Nivoli et al, 2012). Similar to our study, Davis et al (1999) carried out a meta-analysis of 10 double-blind randomized studies comparing relapse rates and found that the difference between the effectiveness of Li and CBZ was nonsignificant: 60% for Li patients and 55% for CBZ.…”
Section: Discussionsupporting
confidence: 58%
“…74 Other recent studies and analyses confirm and extend these conclusions, and add that none of the atypical antipsychotics, despite some having FDA approval for use in maintenance, has convincing evidence of efficacy for that purpose. 75, 76 Ghaemi 75 and Goodwin and colleagues 76 argue that the flaw in the methodology of all the maintenance studies of SGAs is that they start with preselected acute responders to the SGA being tested for maintenance. This "enriched" population of responders is then randomly assigned to either stay on the SGA or switch (often abruptly) to placebo or an active comparator (e.g., lithium).…”
Section: Continued On Next Pagementioning
confidence: 97%
“…Patient and physician biases against it need to be addressed. 75 Because of its narrow therapeutic index, trough serum concentrations of lithium should be closely monitored. The British National Institute for Health and Clinical Excellence guidelines (2006) recommend that levels be taken seven days after initiation and then seven days after every dose or formulation change and the introduction or discontinuation of interacting medications.…”
Section: Continued On Next Pagementioning
confidence: 99%
“…Time to recurrence is often brief, and early episodes are more likely to represent relapses than recurrences. 67 Therefore, it may not be straightforward to draw conclusions about long-term effects from such studies.…”
Section: What Is a Good Indicator Of Treatment Effectiveness?mentioning
confidence: 99%